Brief Overview on Nitinol as Biomaterial - Abdul Wadood (Advances in Materials Science and Engineering)
Shape memory alloys remember their shape due to thermoelastic martensitic phase transformation. These alloys have advantages in terms of large recoverable strain and these alloys can exert continuous force during use. Equiatomic NiTi, also known as nitinol, has a great potential for use as a biomaterial as compared to other conventional materials due to its shape memory and superelastic properties. In this paper, an overview of recent research and development related to NiTi based shape memory alloys is presented. Applications and uses of NiTi based shape memory alloys as biomaterials are discussed. Biocompatibility issues of nitinol and researchers’ approach to overcome this problem are also briefly discussed.